Risk assessment and control measures for machinery in a food production company. - Fu-López, Jayling Selena; Calva Valarezo, Juan Daniel; Pérez Benítez, Hugo Alfredo; López Rocafuerte, Franklin Vicente; Fierro Aguilar, Jaime Patricio (Ingeniería Química y Desarrollo, 2024)
The study analyzed the risks in machinery in a food plant using the HRN matrix to design a safety system based on criticality. Information was collected and each task was analyzed with the HRN matrix to determine criticality. A risk assessment matrix was created, and risks were ranked and prioritized. Action plans were formulated for critical risks, such as guarding and training requirements. The results showed the criticality of certain equipment, such as the laminating machine. Ten percent of the tasks involved high risk, highlighting the need for control. It was concluded that the safety system based on criticality is feasible and would improve safety. A replicable methodology was provided for other plants to analyze risks and implement similar systems. The proposed system has a high potential impact by reducing accidents and absenteeism. It was recommended to analyze the performance of the system, perform a cost-benefit analysis, and extend the model to other critical sectors.
Keywords: Industrial safety; HRN Matrix; Productivity; Criticality; Hazards; Machine guarding; Machine safety